Kajian Modal Sosial Kelompok Tani Tulus Di Desa ponompiaan Kecamatan Dumoga Kabupaten Bolaang Mongondow - Tumbelaka, Kristian Markopolo; Ngangi, Charles Reijnaldo; Sendow, Martha Mareyke (AGRI-SOSIOEKONOMI, 2023)
This research aims to identify and understand social capital in the Tulus Farmer Group in Ponompiaan Village, Dumoga Sub-district, Bolaang Mongondow Regency. The research was conducted for 3 months, from May to July 2023. Data collection methods in this study used primary data and secondary data. Primary data was obtained from direct interviews with members of the Tulus Farmer Group using a list of questions that had been prepared in the form of a questionnaire. Secondary data was obtained from institutions related to the research problem, namely the Ponompiaan Village government. Sampling was done purposively (purposive sampling), the sample taken was the Tulus Farmer Group with a total of 15 farmer group members/respondents. The data analysis method was descriptive qualitative. Based on a survey in the field, the Tulus Farmer Group established good social relations in the form of mutual trust between fellow members and mutual trust between farmer groups and other farmer groups. The highest social capital is in the trust indicator, followed by the social network indicator and finally the social norm indicator.